2019
DOI: 10.1007/s11606-019-05166-5
|View full text |Cite
|
Sign up to set email alerts
|

Nonbacterial Thrombotic Endocarditis Due to Primary Gallbladder Malignancy with Recurrent Stroke Despite Anticoagulation: Case Report and Literature Review

Abstract: Nonbacterial thrombotic endocarditis (NBTE) associated with malignancy is rare; its infrequency and similarity to other diagnoses make it a significant diagnostic challenge. A 63-year-old woman on rivaroxaban for prior deep vein thrombosis presented with left upper extremity weakness and left facial droop with imaging demonstrating multiple strokes. Echocardiograms revealed mitral and aortic valve vegetations. The patient was switched to apixaban and started on vancomycin and ceftriaxone for presumed culture-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…The flow chart of our included studies is shown in Supplementary Figure S1 . Around 25% (39) of included studies were from the USA, and only 1 study was reported from China [ 19 , 22 , 23 , 24 , 27 , 29 , 32 , 33 , 34 , 39 , 41 , 43 , 46 , 47 , 48 , 57 , 58 , 59 , 68 , 69 , 73 , 76 , 81 , 84 , 86 , 88 , 92 , 93 , 94 , 100 , 101 , 105 , 108 , 111 , 114 , 115 , 118 , 131 , 132 , 136 ]. A list of the included studies and the quality assessment are reported in Supplementary Table S2 .…”
Section: Resultsmentioning
confidence: 99%
“…The flow chart of our included studies is shown in Supplementary Figure S1 . Around 25% (39) of included studies were from the USA, and only 1 study was reported from China [ 19 , 22 , 23 , 24 , 27 , 29 , 32 , 33 , 34 , 39 , 41 , 43 , 46 , 47 , 48 , 57 , 58 , 59 , 68 , 69 , 73 , 76 , 81 , 84 , 86 , 88 , 92 , 93 , 94 , 100 , 101 , 105 , 108 , 111 , 114 , 115 , 118 , 131 , 132 , 136 ]. A list of the included studies and the quality assessment are reported in Supplementary Table S2 .…”
Section: Resultsmentioning
confidence: 99%
“… 9 NOACs have not been evaluated and seem inefficient as reported by some case reports in the literature. 12 , 13 , 14 , 15 …”
Section: Discussionmentioning
confidence: 99%
“…In the era of direct oral anticoagulants, there is currently not enough data to support their use in cancer-related NBTE. Recently, a few cases were reported in which patients with cancer-associated NBTE on optimized doses of rivaroxaban had developed multiple discrete embolisms [12] , [13] , [14] .…”
Section: Discussionmentioning
confidence: 99%